Labour Supply and Unemployment Projections for North East India (2011 - 2031) - Khongji, Phrangstone; Nongkynrih, Deigracia (Arthshastra Indian Journal of Economics & Research, 2018)
So far, the studies dealing with labour force and unemployment projections in India remain at the national level, and only a few studies have been undertaken at the state level. There are very little studies in labour force and unemployment projection for North Eastern states of India. In the present study, labour force participation rate and unemployment rate were extrapolated using auto regressive integrated moving average model to obtain the total labour force and unemployed for all the projecting years. The findings revealed that the quantum of an increase in labour force population from 2011 to 2031 for Arunachal Pradesh was 31.1% ; for Assam, it was 41.2% ; for Manipur, it was 47.0% ; for Meghalaya, it was 29.0% ; for Mizoram, it was -0.34% ; for Sikkim, it was 19.4% ; and for Tripura, it was 40.1%. The corresponding increase in the proportion of the unemployed population in the same duration for Arunachal Pradesh was 62.3% ; for Assam, it was 50.3% ; for Manipur, it was 27.1% ; for Meghalaya, it was 66.6% ; for Mizoram, it was 34.8% ; for Sikkim, it was 19.4% ; and for Tripura, it was 50.3%, respectively. One interesting observation, as evident from the projections, was that the gender gap in labor - force participation rate and unemployment rate will permeate further during the years and decades to come. The findings of this paper will help the state governments in formulating the policies to prepare for employment generation in various primary, secondary, and tertiary sectors of the respective state economies.